Clinical-radiological correlation and role of computed tomography staging in chronic rhinosinusitis - Aakanksha Rathor (KeAi Communications Co., Ltd., 2017)
Objective: This study aimed to determine whether there is a clinical-radiological correlation in chronic rhinosinusitis (CRS), to compare operative findings with those of computed tomography (CT) imaging, and to determine the importance of a CT score and staging in management of CRS. Methods: This study is a prospective study. Adult patients meeting diagnostic criteria for CRS were prospectively studied using the Lund–Mackay (LM) symptom score and sinus CT scan. The symptom scores were correlated with CT stage according to the Kennedy and LM staging systems. Similarly, the intraoperative findings were correlated with the Kennedy staging system. The spectrum of anatomical variations in our study population was compared with the findings of symptomatic patients in various other studies. Results: Thirty-four adult patients (13 females, 21 males, mean age: 33 years) met our inclusion criteria. Most of the patients presented with nasal obstruction, headache, and hyposmia. Nasal polyposis was the most common finding in CT scans, with many cases of retention cysts reported as polyps. In total, 50% of patients had a deviated septum. Concha bullosa was the most common finding among the various anatomical variations encroaching the ostiomeatal complex (OMC). In 60%–70% of cases, the CT scan grading correlated with operative findings. LM symptoms scores showed a poor correlation with both LM CT scores and the Kennedy stage. Conclusions: Although CT provided detailed information on sinus involvement; its relation with symptom severity is not reliable. The Kennedy CT staging system correlated better with CRS symptoms. Thus, use of Kennedy staging could be useful to endoscopic sinus surgeons as it provides an insight into the pathophysiology, can guide treatment, and facilitate prognosis prediction in CRS.